Nanocellulose: a bioadsorbent for chemical contaminant remediation - Norrrahim, Mohd Nor Faiz; Kasim, Noor Azilah Mohd; Knight, Victor Feizal; Misenan, Muhammad Syukri Mohamad; Janudin, Nurjahirah; Shah, Noor Aisyah Ahmad; Kasim, Norherdawati; Yusoff, Wan Yusmawati Wan; Noor, Siti Aminah Mohd; Jamal, Siti Hasnawati; Ong, Keat Khim; Yunus, Wan Zin Wan (ROYAL SOC CHEMISTRY, 2021)
Chemical contaminants such as heavy metals, dyes, and organic oils seriously affect the environment and threaten human health. About 2 million tons of waste is released every day into the water system. Heavy metals are the largest contributor which cover about 31% of the total composition of water contaminants. Every day, approximately 14 000 people die due to environmental exposure to selected chemicals. Removal of these contaminants down to safe levels is expensive, high energy and unsustainable by current approaches such as oxidation, biodegradation, photocatalysis, precipitation, reverse osmosis and adsorption. A combination of biosorption and nanotechnology offers a new way to remediate these chemical contaminants. Nanostructured materials are proven to have higher adsorption capacities than the same material in its larger-scale form. Nanocellulose is very promising as a high-performance bioadsorbent due to its interesting characteristics of high adsorption capacity, high mechanical strength, hydrophilic surface chemistry, renewability and biodegradability. It has been proven to have higher adsorption capacity and better binding affinity than other similar materials at the macroscale. The high specific surface area and abundance of hydroxyl groups within lead to the possible functionalization of this material for decontamination purposes. Several research papers have shown the effectiveness of nanocellulose in the remediation of chemical contaminants. This review aims to provide an overview of the most recent developments regarding nanocellulose as an adsorbent for chemical contamination remediation. Recent advancements regarding the modification of nanocellulose to enhance its adsorption efficiency towards heavy metals, dyes and organic oils were highlighted. Moreover, the desorption capability and environmental issue related to every developed nanocellulose-based adsorbent were also tackled.
Keywords: Chemistry